Group photo of San Jose State College 1947 graduates. - Unknown:::Creator::::::::::::
Shirley Orpha Smith and a group of San Jose State College graduates, all wearing full graduation regalia. Shirley Orpha Smith is the fourth from the left and standing in the back.